Mental disorders and the intent to seek help among university students in Iceland - Andrea Una Ferreira 1997-; Marta Silfá Birgisdóttir 1988- (2022)
Background: Young adults' mental health, particularly that of university students, is a growing public health concern. It is critical for those suffering from these disorders to seek treatment because the consequences can be severe. Aims: The current study sought to determine if help-seeking intentions, attitudes, and behaviors differed depending on whether or not university students had previously been diagnosed with depression or anxiety. Current symptoms of anxiety and depression were also examined in relation to which symptoms had the most effects. These issues will also be addressed in terms of gender. Methods: Data from an Icelandic study's questionnaire conducted in 2017 was used in this study that included 375 participants, all of whom were over the age of 18. The mental health questionnaires: Depression Scale (PHQ-9), General Anxiety Disorder (GAD-7), Perceived Stress Scale (PSS-4) and Icelandic Beliefs About Psychological Services (I-BAPS) were utilized in the study. Results: This study discovered that previous help-seeking behavior was associated with stronger intentions to seek help in the future. A strong correlation was found between those that had been diagnosed with either anxiety or depression at some point prior to the study and current symptoms. Results showed that women had more positive attitude towards psychological services than men. Relationship between those with current symptoms of either depression or anxiety and their beliefs about psychological services did not show significant difference. Participants that suffered from depression were most likely to seek help from a medical doctor and the same goes for those with anxiety. Age and help-seeking intentions were compered where age was divided in to three groups and the results revealed a significant difference between the youngest and oldest age groups. When assessing views on expertness based on participants age (using the same age groups), the results were significant between the middle and oldest age groups. Discussion: Mental ...